2014
DOI: 10.2174/1874941001407010008
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Blocking Innicotine High-Responders as a Possible Factor in the Development of Nicotine Dependence?

Abstract: Abstract:Rationale: The importance of reward-associated cues in eliciting behavior is well established, with stimuli associated with drugs of abuse known to play a crucial role in recidivism. Recently, Redish (2004) proposed that drugs, acting as unconditional stimuli (US), remain associable even after being fully predicted by a conditional stimulus (CS), meaning that they are not susceptible to the blocking effect [1]; if correct, this may represent a possible mechanism to explain exaggerated cue-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Deroche-Gamonet et al (2004; see also Kasanetz et al 2010) found that, while all rats would lever-press or nose-poke for cocaine, only a subset would cross a shock to reach the drug, and that same subset showed excessively high progressive ratio breakpoints. Jaffe et al (2014) found that the subset of nicotine-seeking rats that showed excessively high progressive ratio breakpoints also showed a lack of Kamin blocking response to nicotine, even though their Kamin blocking response to food was normal.…”
Section: On Addiction Heterogeneitymentioning
confidence: 97%
“…Deroche-Gamonet et al (2004; see also Kasanetz et al 2010) found that, while all rats would lever-press or nose-poke for cocaine, only a subset would cross a shock to reach the drug, and that same subset showed excessively high progressive ratio breakpoints. Jaffe et al (2014) found that the subset of nicotine-seeking rats that showed excessively high progressive ratio breakpoints also showed a lack of Kamin blocking response to nicotine, even though their Kamin blocking response to food was normal.…”
Section: On Addiction Heterogeneitymentioning
confidence: 97%